ATPase-dependent auto-phosphorylation of the open condensin hinge diminishes DNA binding - Yuko Akai; Ryuta Kanai; Norihiko Nakazawa; Masahiro Ebe; Chikashi Toyoshima; Mitsuhiro Yanagida (Open Biology, 2014)
Condensin, which contains two structural maintenance of chromosome (SMC) subunits and three regulatory non-SMC subunits, is essential for many chromosomal functions, including mitotic chromosome condensation and segregation. The ATPase domain of the SMC subunit comprises two termini connected by a long helical domain that is interrupted by a central hinge. The role of the ATPase domain has remained elusive. Here we report that the condensin SMC subunit of the fission yeast Schizosaccharomyces pombe is phosphorylated in a manner that requires the presence of the intact SMC ATPase Walker motif. Principal phosphorylation sites reside in the conserved, glycine-rich stretch at the hinge interface surrounded by the highly basic DNA-binding patch. Phosphorylation reduces affinity for DNA. Consistently, phosphomimetic mutants produce severe mitotic phenotypes. Structural evidence suggests that prior opening (though slight) of the hinge is necessary for phosphorylation, which is implicated in condensin's dissociation from and its progression along DNA.